Neonatal Thrombocytopenia as a Consequence of Maternal Preeclampsia - Kalagiri, Ram R.; Choudhury, Saiara; Carder, Timothy; Govande, Vinayak; Beeram, Madhava R.; Uddin, M Nasir (American Journal of Perinatology Reports, 2016)
Introduction Preeclampsia (preE) is pregnancy-induced hypertension affecting a significant proportion of pregnant women worldwide and can cause detrimental effects in the mother and newborn. Some of the effects in the newborn include neonatal thrombocytopenia. Pertaining specifically to neonatal thrombocytopenia, several questions remain unanswered.Discussion According to the current literature, neonatal thrombocytopenia due to maternal preE is highly prevalent in the general population and the incidence is reported to be around 30% worldwide. This review gives an insight into the syndrome and summarizes the possible pathological mechanisms, the diagnostic approach, complications, and therapeutic interventions of neonatal thrombocytopenia. It also identifies the involvement of other cell lines, apart from platelets in the newborns. Furthermore, we suggest a future prospective study to investigate the pathogenesis of preE and plan a study involving animal models to come up with a possible therapeutic intervention to prevent preE and its various consequences in neonates.
Keywords: preeclampsia; neonatal thrombocytopenia; pregnancy-induced hypertension